Phytochemical, antibacterial and antifungal activity of rhizome from Anaphyllum wightii.schott against clinical isolates and plant pathogens - Manesh Kunjumon; ShirlyK Thomas; Roshin Elizabeth George; Vaidyanatha Iyer Thankamani (International Journal of Phytomedicine, 2015)
Anaphyllumwightii. Schott is a very rare and endemic threatened plant belonging to the family Areacea. It has been used in the tribal medicine to treat eczema, scabies and as antidote against snakebite.Different solvent extracts of Anaphyllumwightii.Schott were prepared and analysed for phytochemical screening by standard protocols. Antimicrobialactivity was measured using well diffusion method and micro dilution broth method against clinical isolates. The n-butanol and methanol extracts of A. wightii showedsignificant activity against all of the selected microorganisms. Water extract did not show any activity against any of the organisms except Klebsiella sp.The MIC value for leaf n- butanol and methanol were 1.5 mg/ml to 2.5mg/ml and the MBC values were 1.25 to 5 5mg/ml respectively.The antimicrobial activity of rhizome observed in the present study may provide the suggestion that the plant could be a potential source of new and effective antibacterial & antifungal agents. Hence further studies areproposed for the isolation of the antibacterial & antifungal agents from the rhizome extracts of A. wightii.